Exploring Physical Properties of Gravitationally Decoupled Anisotropic Solution in 5D Einstein‐Gauss‐Bonnet Gravity. Issue 10 (16th September 2021) - Maurya, S. K.; Tello‐Ortiz, Francisco; Govender, M.
Abstract: In this paper we present two new classes of solutions describing compact objects within the framework of five‐dimensional Einstein‐Gauss‐Bonnet (EGB) gravity. We employ the Complete Geometric Deformation (CGD) formalism which extends the Minimal Geometric Deformation (MGD) technique adopted in earlier investigations to generate anisotropic models from known isotropic solutions. The two solutions presented arise from mimicking the constraint for the pressure and density respectively which generate independent deformation functions. Rigorous physical tests show that contributions from CDG suppress the effective pressure but enhances the effective density and mass of the compact object, with the suppression/enhancement being modified by the EGB coupling constant. One of the highlights in our findings is that the deformation function along the radial component in CDG is nonzero at the boundary when we mimic both the pressure and density while in MGD we observe a vanishing of this deformation function at the boundary of the fluid configuration only for the pressure constraint. The difference in behavior of the deformation function at the surface predicts different stellar characteristics such as mass‐to‐radius and surface redshifts. Abstract : In this paper two new classes of solutions are presented describing compact objects within the framework of five‐dimensional Einstein‐Gauss‐Bonnet (EGB) gravity. The Complete Geometric Deformation (CGD) formalism will be employed which extends the Minimal Geometric Deformation (MGD) technique adopted in earlier investigations to generate anisotropic models from known isotropic solutions. The two solutions presented arise from mimicking the constraint for the pressure and density respectively which generate independent deformation functions. Rigorous physical tests show that contributions from CDG suppress the effective pressure but enhances the effective density and mass of the compact object, with the suppression/enhancement being modified by the EGB coupling constant. One of the highlights in the findings is that the deformation function along the radial component in CDG is nonzero at the boundary when one mimics both the pressure and density while in MGD one observes a vanishing of this deformation function at the boundary of the fluid configuration only for the pressure constraint. The difference in behavior of the deformation function at the surface predicts different stellar characteristics such as mass‐to‐radius and surface redshifts.